Thermal diffusivity of kaolinite–mullite ceramic matrix composite with silicon nitride nanoparticle filler - See, Alex; Hassan, Jumiah; Hashim, Mansor; Abdul Wahab, Zaidan (Elsevier, 2014)
Thermal diffusivity of mullite fused ceramics was determined from room temperature up to 500 °C at intervals of 100 °C. The ceramic material was formed by combining kaolinite as the matrix and silicon nitride as the filler powder. The ceramics were sintered at 1000 °C, 1100 °C, and 1200 °C to study the structural differences. Thermal diffusivity data showed that the addition of silicon nitride affects the composites heat flow and this behavior is noticeable at 1100 °C and 1200 °C samples. The thermal diffusivity data was plotted on 1000/T graph to demonstrate a linear relation for filler effects of silicon nitride on the mullite matrix. Additions of 25% and 30% silicon nitride sintered at 1200 °C exhibited thermal diffusivity values lower than pure mullite crystal at 0.55–0.45 mm2/s. These values suggest that heat conduction across the system was interrupted by silicon nitride nanoparticle additions via micropore formations. These samples have potential applications for high temperature thermal insulation.